1999
DOI: 10.1017/s0967199499000611
|View full text |Cite
|
Sign up to set email alerts
|

Oocyte activation and parthenogenetic development of bovine oocytes following intracytoplasmic sperm injection

Abstract: Development of bovine oocytes after intracytoplasmic sperm injection (ICSI) was investigated. Oocytes were matured for 24–26 h in vitro and injected with isolated sperm heads. When treated with 7% ethanol (v/v) for 5 min, 71.7% of ICSI oocytes were activated as shown by the resumption of meiosis and the formation of female pronuclei. However, 41.5% of injected sperm heads remained condensed at 18–20 h after injection into the ooplasm. The incidence of decondensing sperm and that of male pronuclei at this stage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 25 publications
0
24
0
2
Order By: Relevance
“…One disadvantage of the application of exogenous activation is to increase the possibility of the parthenogenetic development [41]. In the present study, only a few blastocysts (1-2%) were obtained during 8-days culture after chemical or physical parthenogenetic treatments (Table 2).…”
Section: Discussionmentioning
confidence: 66%
“…One disadvantage of the application of exogenous activation is to increase the possibility of the parthenogenetic development [41]. In the present study, only a few blastocysts (1-2%) were obtained during 8-days culture after chemical or physical parthenogenetic treatments (Table 2).…”
Section: Discussionmentioning
confidence: 66%
“…Presence of exogenous plasmid DNA in LI, IVF and ICSI embryos was determined by PCR, and localization of exogenous DNA into their nuclei was confirmed by FISH in ICSIderived embryos. Chemical activation following nontransgenic ICSI has been reported to improve bovine embryo development [20][21][22][23][24]. We also demonstrated that the activation in transgenic ICSI improves embryo development [25], showing different outcomes according to the chemical activation treatments [26].…”
mentioning
confidence: 67%
“…In domestic species, it has been reported that failed or abnormal decondensation of sperm chromatin is frequency observed in oocytes injected with intact sperm [33,34]. Katayama et al [35] showed that oocyte activation and decondensation of sperm chromatin are delayed after injection of intact spermatozoa, which is due to the existence of the sperm plasma membrane.…”
Section: Discussionmentioning
confidence: 99%